(untitled) (Journal of Brahmanbaria Medical College, 2026)
Background: Blood Stream Infections (BSIs) are a significant cause of illness and death among pediatric patients worldwide, particularly in middle-income countries like Bangladesh. Understanding the common bacterial pathogens responsible for BSIs and their antibiotic resistance patterns is critical to improving clinical outcomes. This study aims to identify the common bacterial pathogens causing blood culture confirmed BSIs in pediatric patients admitted to a tertiary care hospital in Bangladesh. Materials and methods: This cross-sectional study was conducted during the period from January to December 2024 at the Outpatient Pediatric Department of Women’s Medical College Hospital, Dhaka, Bangladesh. Blood samples were collected from suspected pediatric patients having bloodstream infections. Bacterial isolates were identified using standard microbiological techniques. Antibiotic susceptibility testing was performed according to Clinical and Laboratory Standards Institute guidelines. The distribution of pathogens was analyzed across different age groups and by gender. Statistical analysis was done to assess associations between demographic variables and pathogen types. Results: Among 58 positive blood cultures, Staphylococcus aureus was the most common pathogen (27.4%) followed by Escherichia coli (23.9%) Klebsiella pneumoniae (22.2%) and Streptococcus pneumoniae (15.4%). S. aureus infections were significantly more frequent in male patients (p=0.045) while age was not significantly associated with pathogen type. High resistance rates were observed against Ciprofloxacin, Cefotaxime, Penicillin and Oxacillin. E. coli showed lower resistance to Imipenem (5%) and higher resistance to Ciprofloxacin (60%) and Cefotaxime (55%). S. pneumoniae was fully sensitive to Vancomycin (100%) but highly resistant to Penicillin (85%). K. pneumoniae exhibited 50% resistance to Ceftriaxone and S. aureus showed 70% Oxacillin resistance and 25% Vancomycin resistance. Pediatric BSIs in this setting are dominated by S. aureus, with a high prevalence of multidrug-resistant pathogens. Conclusion: Continuous local surveillance, rational antibiotic use and strengthened infection control measures are essential to optimize empiric therapy and improve pediatric treatment outcomes. JBRMC, Volume 08 Issue 01 January 2026 ; 20-24